Analysis of Management Function on Health Protocol in the Medan City Traditional Market Environment - Widiya Nisa; Juanita Juanita; Siti Khadijah Nasution (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is analysis of management function on health protocol in the Medan City Traditional Market Environment. This study uses a qualitative research method with a phenomenological design. This research is conduct in the Medan City Traditional Market Environment. This research is conduct from February to April, 2022. The informants in this study are market managers, traders, and visitors. Qualitative data analysis in this study uses Cresswell's theory which consists of organizing and preparing data for analysis, read or look at all the data, start coding all of the data, used coding process to generate a description, interrelating themes, and interpreting the meaning of themes. The results of the study indicate that management function to support all activities arranged based on needs has not run consistently. To market managers to be consistent in meeting the needs for implementing health protocols and having a high commitment to supporting the implementation of health protocols in the market by forming a special team in implementing health protocol policies, making standard operating procedures for implementing health protocols, providing the necessary infrastructure and continuously carry out socialization, supervision and discipline in order to improve compliance in the market and can implement health protocols in accordance with the health protocol policies that have been contained in Mayor Regulation Number 27 of 2020.